Vortex induced vibration energy harvesting using magnetically coupled broadband circular-array piezoelectric patch: Modelling, parametric study, and experiments. (15th January 2023) - Hafizh, Muhammad; Muthalif, Asan G.A.; Renno, Jamil; Paurobally, M.R.; Bahadur, Issam; Ouakad, Hassen; Sultan Mohamed Ali, Mohamed
Highlights: A submerged vortex-induced vibration-based piezoelectric energy harvesting for pipeline applications was proposed. A computational parametric study investigated the different coupler shapes best to increase the oscillations of a bluff body with hollow and solid volumes. A circular array arrangement can increase the energy harvested by adjusting the synchronization frequency to the flow velocity of the transport medium with a measured combined output of 9 V. Experimentally demonstrated the effects of nonlinearity using magnetic tip coupling on the bluff body. Peak output and bandwidth can be adjusted with magnet separation distance by up to 93% and 33%, respectively. Abstract: Piezoelectric composites have become increasingly important in energy harvesting from vibration and, more recently, flow-induced vibration. The compatibility of piezoelectric devices has allowed tuning harvesters to the system's natural frequency to maximize the energy harvesting performance. However, the narrowband characteristic in piezoelectric composites is susceptible to efficiency losses when there are changes in the ambient surrounding. Thus, magnetic coupling introduces nonlinearity and can increase the broadband energy harvesting performance to account for slight variations. This paper proposes a piezoelectric energy harvester used in a pipe array to harvest oscillations from vortex-induced vibration. Adding a magnetic coupler introduces bandwidth enhancement characteristics that can accommodate slight changes in the freestream velocity. A computational simulation was used to compare different coupler shapes that can direct water flow toward the harvester array. The results show that an elliptical coupler works best and that a solid coupler has up to 50 % better performance than a hollow coupler. The experimental results showed that narrowband voltage output could reach up to 9 V in a pipe array. Furthermore, the broadband performance of magnetic coupling increased the bandwidth by up to 33 % in different orientations and distances.